1998
DOI: 10.5465/ame.1998.650515
|View full text |Cite
|
Sign up to set email alerts
|

Proactive corporate environmental management: A new industrial revolution

Abstract: Executive Oyerview Corporofions in North America, Europe. lapan. and in mqst newly industrializing notions are embracing environmental protection crs port of their internofjonal competitive strategies. For many firms, the shift to proactive environmental monogement is driven by pressures from governments, customers, employees, and competitors. Boih consumers and investors are beginning lo see more clearly the relofionship between business performance ond environmenfol quality. The,trend toward proactive enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
498
0
29

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 575 publications
(535 citation statements)
references
References 11 publications
8
498
0
29
Order By: Relevance
“…A consistent body of research can be found in the general management and business strategy literature, that analyses the role of people involved within the organization in promoting a sustainability orientation: various issues have been investigated such as the role of top management's values in determining sustainability orientation (Berry and Rondinelli 1998;Quazi 2003), entrepreneurial commitment to sustainability (Shaltegger 2002) or management practices and principles reshaped by a sustainability orientation (Atkin et al 2012;Warner 2007).…”
Section: Entrepreneurs and Top Managementmentioning
confidence: 99%
“…A consistent body of research can be found in the general management and business strategy literature, that analyses the role of people involved within the organization in promoting a sustainability orientation: various issues have been investigated such as the role of top management's values in determining sustainability orientation (Berry and Rondinelli 1998;Quazi 2003), entrepreneurial commitment to sustainability (Shaltegger 2002) or management practices and principles reshaped by a sustainability orientation (Atkin et al 2012;Warner 2007).…”
Section: Entrepreneurs and Top Managementmentioning
confidence: 99%
“…Attitudes are recognized for seriously affecting decision-making and resource allocation to specific actions to deal with environmental issues (Bansal and Roth, 2000;Colwell and Joshi, 2013). Managers' environmental attitudes and commitments further affect how they coordinate and encourage collaboration among different divisions and departments (González-Benito and González-Benito, 2006), how environmental leadership is reflected in the formulation of new environmental policies and goals (Berry and Rondinelli, 1998), and the extent to which institutional pressures are converted into positive environmental actions (Colwell and Joshi, 2013). Likewise, managerial opinions about the potential outcomes of environmental management count in the consequences on economic performance (Wagner and Schaltegger, 2004).…”
Section: Managerial Attitutes and Strategic Intentmentioning
confidence: 99%
“…Strategic environmental management and its outcomes have been addressed from different perspectives, ranging from the application of green technologies as a means to gain competitive advantage (Shrivastava, 1995) to the perception of environmental regulation as a driver for innovation and improvement of the competitive position (Porter and van der Linde, 1995). Likewise, several motivators of environmental action have been addressed to understand the extent of influence of organizational, institutional and attitudinal forces (Berry and Rondinelli, 1998;Bansal and Roth, 2000;Banerjee et al, 2003;Paulraj, 2009;Colwell and Joshi, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Nos últimos anos, tem crescido o número de estudiosos que argumentam que, para alcançar vantagem competitiva, torna-se necessário que as empresas maximizem seu retorno ao mesmo tempo que desenvolvem progressos em relação à implementação de práticas ambientais nos negócios (LEE, 2009;BERRY;RONDINELLI, 1998;PORTER;VAN DER LINDE, 1995). Essa conexão é baseada no número de pesquisas que concluíram que uma estratégia ambiental proativa lidera o desenvolvimento de importantes capacidades organizacionais que podem elevar a competitividade das indústrias (ARAGON-CORREA; SHARMA, 2003;BERRY;RONDINELLI, 1998;SHARMA;VREDENBERG, 1998).…”
Section: Fundamentos Teóricos Estratégias De Gestão Ambiental E Seus unclassified
“…Essa conexão é baseada no número de pesquisas que concluíram que uma estratégia ambiental proativa lidera o desenvolvimento de importantes capacidades organizacionais que podem elevar a competitividade das indústrias (ARAGON-CORREA; SHARMA, 2003;BERRY;RONDINELLI, 1998;SHARMA;VREDENBERG, 1998). Como resultado, muitos estudiosos da literatura corrente têm concluído que as empresas ISSN 0034-7590 artigos • EstratÉgias DE gEstÃo aMBiENtaL E sEUs FatorEs DEtErMiNaNtEs: UMa aNÁLisE iNstitUCioNaL precisam incorporar questões relativas ao ambiente natural no âmago de suas estratégias competitivas.…”
Section: Fundamentos Teóricos Estratégias De Gestão Ambiental E Seus unclassified